Perspektif Teologi Paulus Tentang Pemberitaan Salib Kristus Dalam 1 Korintus 1:18-25 - Manuputty, Mozes; Setiawan, Tjutjun; Agus Indratno, Yohanes Twintarto (STT INDONESIA MANADO, 2024)
Abstract: The words about the cross of Christ and its preaching are an urgent part of biblical theology. The words about the cross emphasize the status of Jesus who incarnated (John 1:14) or the humble status of Jesus in the ‘likeness’ (Gk. MORPHE), of a servant (Gk. DOULOS), and being equal to humans (Phil. 2:7). Without Jesus being incarnated, there would be no teaching about the cross of Jesus in the Bible, either in descriptive, prophetic and type forms in the Old Testament and then executed through the incarnation of Jesus with the most important work in the history of human life, which is the Cross of Christ. This research examines Paul’s theological perspective regarding the preaching of the cross of Christ in 1 Corinthians 1:18-25. The method used is a qualitative literature study with an exegetical description orientation. The research findings show that the cross of Christ redeems because it is based on God’s wisdom. The important thing and prominent thing that is emphasized is that the cross of Christ that Paul preaches is very exclusive, unique, and anti-thetical because it is Gospel-centered, which is the only good news, which will not be the same as any preaching of any other religion, and any philosophy. Abstrak: Berita tentang salib Kristus dan pemberitaannya merupakan bagian urgen di dalam teologi biblikal. Berita tentang salib mengedepankan status Yesus yang berinkarnasi (Yoh. 1:14) atau status kerendahan Yesus di dalam ‘rupa’ (Yun. MORPHE), seorang hamba (Yun. DOULOS), dan menjadi sama dengan manusia (Fil. 2:7). Tanpa Yesus berinkarnasi, maka tidak ada ajaran tentang salib Yesus di dalam Alkitab, baik dalam bentuk deskriptif, nubuatan, dan tipe di dalam Perjanjian Lama dan kemudian dieksekusi melalui inkarnasi Yesus dengan karya terpenting di dalam sejarah kehidupan manusia, yakni Salib Kristus. Penelitian ini bertujuan mengkaji bagaimana perspektif teologi Paulus tentang pemberitaan salib Kristus dalam 1 Korintus 1:18-25. Metode yang dipakai adalah kualitatif studi pustaka dengan orientasi mendeskripsikan secara eksegetikal. Adapun temuan penelitian yang didapat adalah bahwa salib Kristus itu menyelamatkan karena berbasiskan hikmat Allah. Hal penting dan menonjol yang sangat ditekankan adalah bahwa salib Kristus yang Paulus beritakan sangat bersifat atau bercirikan eksklusivitas, unik, dan anti-tesis, oleh karena berpusat pada Injil, yang merupakan kabar baik satu-satunya, yang tidak akan sama dengan pemberitaan agama manapun dan filsafat apa pun.